Bandage Contact Lens Associated Infection after Amnion Membrane Transplantation in Peripheral Ulcerative Keratitis Case with Spondyloarthritis - Permatasari, Devi Sarah Intan; Zuhria, Ismi; Rahmawati, Lita Diah (Vision Science and Eye Health Journal, 2024)
Introduction: Bacterial keratitis causes around 90% of all cases of microbial keratitis. The global rise in contact lens usage has contributed to an increased risk of microbial keratitis. Peripheral ulcerative keratitis (PUK) is essential to diagnose as it can be the first presenting feature of a sight-threatening and associated with rheumatic autoimmune disease. Case Presentation: The case presents a 35-year-old woman with redness, discharge, and tenderness in her right eye (RE) since the day before, along with light sensitivity and tearing. Three months prior, she underwent multilayer amniotic membrane transplantation (AMT) surgery for corneal thinning due to peripheral ulcerative keratitis (PUK) and wore a contact lens postoperatively as a bandage. She had a history of conjunctival resection related to the PUK a year ago. She received oral cyclosporin and methylprednisolone for spondyloarthritis. Initially, her visual acuity of the RE was limited to hand movement. Diagnosis included RE keratoconjunctivitis related to contact lens and PUK post-AMT surgery; treatment comprised intravenous and topical antibiotics, artificial tears, cycloplegics, analgesics, and oral ascorbic acid. After four days of treatment, clinical signs were improved, with visual acuity progressing from hand movement to counting fingers at one meter. Conclusions: Careful management is essential for PUK patients after AMT surgery, especially those using contact lenses as bandages due to the potential risk of infection. Early PUK identification is crucial, as it may indicate sight-threatening issues and underlying systemic diseases. Meticulous examination and multidisciplinary management are required to ensure patient safety.